VARIABILITY OF CHARACTERS OF WINTER GARLIC VARIETIES UNDER THE CONDITIONS OF FOREST-STEPPE OF THE ALTAI REGIONS' OB RIVER AREA - S. V. Zharkova; S. M. Sirota; N. M. Velizhanov (Овощи России, 2018)
The variability or stability of economically valuable features of varieties under cultivation conditions are very important indices. Environmental factors affect plants throughout the entire growing season. The research goal is to study the changes and stabilization of the characters that determine the phenotype of winter garlic when sampling from the variety accessions in the forest-steppe of the Altai Regions' Ob River Area. In the course of research from 2003 through 2007, the local forms and variety accessions from various regions of Russia were studied. The research was carried out according to the methodology guidelines. The variability of seven quantitative characters was investigated. In our study, the most stable characters were the "number of leaves" and "leaf length". The characters "number of cloves in a bulb" and "clove weight" are very difficult to stabilize. The variability of these indices was mainly medium and high. The characters with insignificant variability coefficient under the conditions of the south of West Siberia were revealed. The percentage of the factors' influence on the variability of the "bulb weight" character was determined. The following most stable variety accessions for the conditions of the forest-steppe of the Altai Regions' Ob River Area were identified: the varieties Skif, Kasmala and German, and the local forms K 3 and K 56.